2021
DOI: 10.1080/19932820.2021.1921900
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of violence against women in Kairouan, Tunisia, in 2017

Abstract: Violence against women represents a serious concern worldwide. In Tunisia, despite an advanced legislative framework, we still receive women victims of violence. This survey aimed to characterize the demographic and clinical profile of women victims of violence in Kairouan, central Tunisia. This survey was designed as a cross-sectional study. It concerned women victims of violence over 18 years old, consulting the emergency department of the University Hospital of Kairouan during 3 months in 2017. We defined v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…Both in the results presented here and in the literature (18,29,30) , the positive relationship between drug use, legal or illicit, with the occurrence of violence against women, was perceived, thus requiring, therefore, that health professionals are prepared to work in the context of primary prevention, with the identification of risk factors associated with the occurrence of violence, assessing women and their context of social life, as in the context of secondary prevention, providing adequate care to victims of violence from physical care to mental health dimensions, avoiding the victim's feeling of guilt and dependence on substance use, as well as implementing strategies to prevent the recurrence of events (18) .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Both in the results presented here and in the literature (18,29,30) , the positive relationship between drug use, legal or illicit, with the occurrence of violence against women, was perceived, thus requiring, therefore, that health professionals are prepared to work in the context of primary prevention, with the identification of risk factors associated with the occurrence of violence, assessing women and their context of social life, as in the context of secondary prevention, providing adequate care to victims of violence from physical care to mental health dimensions, avoiding the victim's feeling of guilt and dependence on substance use, as well as implementing strategies to prevent the recurrence of events (18) .…”
Section: Discussionsupporting
confidence: 67%
“…A second review study showed that the non-white skin color dimension seems to have a positive association with psychological violence, as well as the marital status of not being married seems to be related to a higher prevalence of psychological and physical/sexual violence (3) . The low education dimension was associated with the occurrence of violence in a study carried out in Vitória, Espírito Santo, with women in Primary Care, in which the occurrence of psychological (57%), physical (39.3%) and sexual (18) violence was identified. %) among women throughout life (13) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…O aspecto da ocupação da dimensão social também foi avaliado em outro estudo nacional (16) , em que foi obtido que a maioria das mulheres vítimas de violência investigadas possuíam algum emprego formal ou não. Contudo, outros estudos sugerem que ser dona de casa ou estar mais tempo em casa aumenta consideravelmente as chances da mulher de sofrer algum tipo de violência, em decorrência dos altos índices de violência doméstica (17)(18)(19) . Ainda, o aspecto religião, vinculado à dimensão social, mostrou estar mais associado às violências psicológica e sexual, enquanto que a dimensão renda esteve relacionada à ocorrência de violência física.…”
Section: Discussionunclassified
“…Tanto nos resultados aqui apresentados como na literatura (18,29,30) , foi percebida a relação positiva entre o uso de drogas, lícitas ou ilícitas, com a ocorrência de violência à mulher, necessitando, portanto, que os profissionais de saúde estejam preparados para atuar no contexto da prevenção primária, com a identificação dos fatores de risco associados à ocorrência da violência, avaliando a mulher e seu contexto de vida social, como no contexto da prevenção secundária, prestando um cuidado adequado às vítimas de violência desde em relação ao cuidado físico até às dimensões de saúde mental, evitando o sentimento de culpabilização da vítima e a dependência do uso de substâncias, assim como implementando estratégias para evitar a recorrência dos eventos (18) .…”
Section: Discussionunclassified